Patient race and racial composition of delivery unit associated with disparities in severe maternal morbidity: a multistate analysis 2007–2014. (August 2021) - Sastow, D.L.; Jiang, S.Y.; Tangel, V.E.; Matthews, K.C.; Abramovitz, S.E.; Oxford-Horrey, C.M.; White, R.S.
Highlights: A study of hospital-level factors and severe maternal morbidity (SMM). Delivering at majority Black-serving hospitals was associated with increases in SMM. Delivering at high safety-net burden hospitals was not associated with SMM. Effect modification exists between hospital and patient level determinants and SMM. Abstract: Background: High Black-serving delivery units and high hospital safety-net burden have been associated with poorer patient outcomes. We examine these hospital-level factors and their association with severe maternal morbidity (SMM), independently and as effect modifiers of patient-level factors. Methods: Using the 2007–2014 State Inpatient Databases (Florida, New York, California, Maryland, Kentucky), we analyzed delivery hospitalizations. We constructed generalized linear mixed models with patient- and hospital-level variables (Black-serving delivery units: high: top 5th percentile; medium: 5th-25th percentile; low: bottom 75th percentile; hospital safety-net burden status defined by insurance status) and report adjusted odds ratios (aOR) and 99% confidence intervals (CI). We repeated our mixed models with stratification and interaction analysis. Results: 6 879 332 delivery hospitalizations were included in the analysis. Deliveries at high (aOR 1.83; 99% CI 1.34 to2.50) or medium (aOR 1.27; 99% CI 1.10 to 1.46) Black-serving delivery units were more likely to have SMM than deliveries at low Black-serving delivery units. Hospital safety-net burden was not significantly associated with SMM. In stratified models by hospital category, deliveries of Black women were associated with an increase in SMM compared with deliveries of White women in all hospital categories. In interaction models, Black women giving birth in high Black-serving delivery units had more than twice the odds of White women in low Black-serving delivery units of experiencing SMM (aOR 2.42; 99% CI 1.90 to 3.08). Conclusion: The patient racial/ethnic composition of the delivery unit is associated with adjusted-odds of SMM, both independently and interactively with individual patient race.